UTILIZATION OF BOILED MORINGA LEAF WATER TO INCREASE BREAST MILK PRODUCTION POSTPARTUM MOTHERS AT TANJUNG LEIDONG PUBLIC HEALTH CENTER - Harahap, Maya Surya Ningsih; Herna Rinayani Manurung; Lasria Simamora; Tiara Dinda Lestari Siregar; Rismawati Pasaribu; Siska Heriani; Sabbiah (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Low breast milk production is a challenge for postpartum mothers in meeting their babies’ nutritional needs, especially in the first six months of life. Various efforts have been made to increase breast milk production, one of which is through the consumption of boiled water from Moringa oleifera leaves, known as a natural galactagogue. Objective: To determine the effectiveness of using boiled water from Moringa leaves on increasing breast milk production in postpartum mothers. Method: This study used a pre-experimental design with a one-group pretest-posttest approach. A sample of 20 postpartum mothers who met the inclusion criteria were given an intervention of boiled water from Moringa leaves twice daily for seven days. Breast milk production was measured before and after the intervention using a breast milk volume observation sheet. Results: A paired t-test showed significant results with a p-value of 0.000. Conclusion: Boiled water from Moringa leaves is effective in increasing breast milk production in postpartum mothers.